Implementasi Pembelajaran Pendidikan Agama Islam pada Kelas 10 Sekolah Inklusi - Enoh Nuroni Enoh Nuroni; Nurul Afrianti; Robi Mochamad Ilham (Bandung Conference Series: Islamic Education, 2023)
Abstract. Islamic Islamic Religious Education (PAI) is a conscious and planned effort to prepare students to believe, understand, live, and practice the teachings of Islam through guidance, teaching, and practice activities. Education, particularly Islamic Religious Education (PAI), is provided to children who are not only physically complete but also to children who have physical or mental disorders or deficiencies. Nature High School Bandung is an educational institution that has implemented an inclusive education program because there are children with special needs (ABK) who learn together with other normal children, of course with different learning models. This school is able to accept both regular students and students with special needs, known as "inclusion," which is the choice of parents to entrust their children to an inclusive school education so they can participate in learning with other normal children. Islamic Religious Education (PAI) teaching and learning activities are the same as in general; there is no difference between normal students and students with special needs. This research is a type of qualitative research, namely field research. Researchers also use various theories for this qualitative research. Researchers will observe the inclusion learning process that takes place at SMPIT Alam Permata, starting from learning planning, implementation, assessment, and supervision of learning. In this qualitative study, researchers collected data by observation, interview, and documentation. The result of this study is the implementation of Islamic Religious Education (PAI) inclusion learning in grade 10 at Sekolah Alam High School Bandung, which consists of learning planning, learning process, and evaluation of Islamic Religious Education (PAI) inclusion learning in Inclusion Education. Abstrak. Pendidikan Agama Islam (PAI) merupakan usaha sadar dan terencana untuk menyiapkan siswa dalam meyakini, memahami, menghayati dan mengamalkan ajaran Islam melalui kegiatan bimbingan, pengajaran dan latihan. Pendidikan, khususnya Pendidikan Agama Islam (PAI) tidak hanya diberikan kepada anak yang mempunyai kelengkapan fisik saja, akan tetapi juga diberikan kepada anak yang mempunyai kelainan dan kekurangan fisik atau mental. Sekolah Alam Bandung adalah lembaga pendidikan yang telah melaksanakan program pendidikan inklusi karena didalamnya terdapat Anak Berkebutuhan Khusus (ABK) yang belajar bersama-sama anak normal lainnya, tentunya dengan model pembelajaran yang berbeda. Sekolah ini mampu menerima siswa reguler maupun siswa berkebutuhan khusus yang disebut dengan inklusi yang mana sekolah ini menjadi pilihan orang tua siswa untuk menitipkan anaknya pada pendidikan sekolah inklusi untuk mengikuti pembelajaran dengan anak normal lainnya. Kegiatan belajar mengajar Pendidikan Agama Islam (PAI) sama seperti pada umumnya tidak ada perbedaan antara siswa normal maupun siswa berkebutuhan khusus. Penelitian ini merupakan jenis penelitian kualitatif, yakni penelitian lapangan. Peneliti juga menggunakan berbagai teori untuk penelitian kualitatif ini. Peneliti akan mengamati proses pembelajaran inklusi yang berlangsung di Sekolah Alam Bandung tingkat SMA ini, mulai dari perencanaan pembelajaran, pelaksanaannya, penilaian dan pengawasan pembelajarannya. Dalam penelitian kualitatif ini, peneliti mengumpulkan data dengan observasi, wawancara dan dokumentasi. Hasil dari penelitian ini adalah implementasi pembelajaran inklusi Pendidikan Agama Islam (PAI) pada kelas 10 di SMA Sekolah Alam Bandung yang terdiri dari Perencanaan Pembelajaran, Proses Pembelajaran dan Evaluasi Pembelajaran Pendidikan Agama Islam (PAI) dalam Pendidikan Inklusi.